An organic solar cell containing liquid crystal and a method for preparing the same
Patent Information
- Application Number
- CN202611042614.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-23
AI Technical Summary
但是另一方面,从热力学本质考虑,TCC的存在表明材料具有进一步结晶的热力学驱动力,在器件工作时,当受到热应力或光诱导应力激发时,这种亚稳态可能会导致逐渐的相分离、缺陷形成以及非辐射复合增强,从而加速器件性能衰退
[0035](3)实现高效率与高稳定性的协同提升:本发明制备的有机太阳能电池器件同时获得了显著提升的光电转换效率和优异的长期稳定性。如在经3UTPP4处理的PM6:BTP-eC9二元体系中,器件的光电转换效率从18.61%提升至19.57%,填充因子从约78.52%提升至80.31%;结合二碘苯添加剂结合使用,填充因子进一步提升到80.51%,光电转换效率进一步提升到20.07%。在经3UTPP4处理的D18:L8-BO二元体系中,结合二碘苯添加剂共同使用,器件的光电转换效率进一步提升至20.73%,填充因子达到82.14%。稳定性方面,本发明制备的器件在氮气氛围下存储1600小时后,仍能保持初始PCE的96%,远高于对照器件的91%;在45℃、1个太阳光强下进行最大功率点跟踪1000小时后,仍能保持81%的初始效率,显著优于对照器件的69%。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic photovoltaic technology, specifically relating to an organic solar cell containing liquid crystal and its preparation method. Background Technology
[0002] Solar energy, as an environmentally friendly and abundant renewable energy source, has seen photovoltaic (PV) power generation technology become an important component of current renewable energy technologies, particularly in its application to human production and daily life. In recent years, among numerous new types of solar cells, organic solar cells (OSCs) have gradually attracted attention. Compared to traditional crystalline silicon solar cells, OSCs possess unique characteristics such as lightweight, translucency, color variety, flexibility, and roll-to-roll mass production. They can be bent and twisted within buildings or clothing and can be made in any color, even translucent, to blend seamlessly with the surrounding environment. Their potential applications in future wearable device power supply, building-integrated photovoltaics (BIPV), and military fields promise to be a powerful complement to silicon solar cells.
[0003] In recent years, with the continuous reports of new materials and device technologies, the photoelectric conversion efficiency of organic solar cells has been steadily improving, with the highest laboratory efficiency exceeding 20%, initially reaching commercialization standards. However, the commercial application of organic solar cells still faces two major challenges: low efficiency and poor stability. Therefore, developing high-efficiency and high-stability organic solar cells is crucial for their application.
[0004] Currently, commonly used strategies to improve the efficiency of organic solar cells include additives [Adv. Mater. 2021, 33,2100830; Energy Environ. Sci. 2025, 18, 313; Adv. Mater. 2019, 31, 1900477], ternary strategies [Energy Environ. Sci. 2022, 15, 384; Nat. Energy 2023, 8, 978; Nat. Commun. 2024, 15, 8872], and post-processing strategies (such as thermal annealing and solvent annealing) [Adv. Mater. 2024,36, 2411957; Adv. Mater. 2020, 32, 2005386]. It is worth noting that volatile additives have been able to increase the power conversion efficiency (PCE) of organic photovoltaic devices to nearly 21% [Nat. Energy 2025, 10, 1251]. However, volatile additives need to be completely removed from the active layer; otherwise, they will cause instability in the morphology of the active layer, reducing efficiency and stability. This leads to the complexity and cumbersomeness of the battery fabrication process.
[0005] Since 2019, the discovery of acceptor-donor-receptor (A-DA'DA) type acceptors, represented by Y6 [Joule 2019, 3, 1140], has greatly accelerated the research and development of organic solar cells. The three-dimensional stacked structure and high molecular weight (between polymers and small molecules) of A-DA'DA type acceptors endow them with unique thermal properties, such as high melting points, occasional secondary phase transitions, and cold crystallization temperatures. These unique thermal properties affect the active layer and the performance of the solar cells. For example, the representative high-performance material L8-BO(T... m =319 °C) shows higher performance than Y6 (T m With a melting point of 298 °C, it exhibits higher crystallinity and more ordered molecular stacking, significantly improving device performance. Another highly efficient A-DA'DA type acceptor, BTP-eC9, shows significant cold crystallization behavior (Tcc) around 195 °C and a melting point of 300 °C. The presence of this cold crystallization temperature indicates that the film initially forms in a thermodynamically metastable state, possessing the potential to further crystallize into a more ordered structure. It is noteworthy that T... CC The stability of organic solar cells is mainly reflected in two aspects. Firstly, the high Tg of the acceptor material... CC Typically associated with a higher glass transition temperature (T). gThe correlation, corresponding to suppressed molecular motion, to some extent indicates that the active layer film has good morphological stability. However, on the other hand, considering the thermodynamic essence, T... CC The presence of these metastable states indicates that the material possesses a thermodynamic driving force for further crystallization. During device operation, when subjected to thermal or photoinduced stress, this metastable state may lead to gradual phase separation, defect formation, and nonradiative recombination enhancement, thereby accelerating device performance degradation. Therefore, suppressing the formation of such metastable states and achieving thermodynamically stable bulk heterojunction morphologies during thin film preparation is crucial for realizing high-efficiency and long-term stable organic photovoltaic devices. Summary of the Invention
[0006] In view of the defects or deficiencies of the prior art, the present invention provides an organic solar cell containing liquid crystal.
[0007] Therefore, the photoactive layer of the organic solar cell provided by the present invention includes an electron donor material, an electron acceptor material, and a liquid crystal compound, wherein the general structural formula of the liquid crystal compound is Formula I:
[0008]
[0009] Formula I Where R1 and R2 are each independently C1-C 10 Straight-chain alkyl or C1-C 10 Branched alkyl groups.
[0010] Alternatively, the liquid crystal compound may have a melting point of 30-100 °C and a clearing point of 100-180 °C.
[0011] An alternative is that, when R1 is propyl and R2 is butyl, the structural formula of the liquid crystal compound is Formula II:
[0012] Formula II.
[0013] An alternative is that, when R1 is ethyl and R2 is propyl, the structural formula of the liquid crystal molecule is Formula III:
[0014] Formula III.
[0015] An alternative is that, when R1 is propyl and R2 is ethyl, the structural formula of the liquid crystal compound is Formula IV:
[0016] Formula IV.
[0017] An alternative is that, when R1 is butyl and R2 is propyl, the structural formula of the liquid crystal compound is formula V:
[0018] Formula V.
[0019] An alternative is that, when R1 is pentyl and R2 is propyl, the liquid crystal compound has the structural formula of Formula VI:
[0020] Formula VI.
[0021] Alternatively, the electron donor material may be one or more of the following: D18, PM6, PTQ10, D18-Cl, P3HT, PTB7-Th, PTB7, PBDB-T, and J52 (Formula VII); and the electron acceptor material may be one or more of the following: Y6, BTP-eC9, L8-BO, Y6-BO, BTP-eC11, BTP-4Cl, N3, PYT, and PY-IT (Formula VIII).
[0022]
[0023] Equation VII
[0024] Formula VIII An alternative approach is to use an electron donor material and an electron acceptor material with a mass ratio of 1:1 to 1:1.3, and to add liquid crystal molecules at a mass of 1% to 10% of the electron donor material.
[0025] Alternatively, the solar cell may include a substrate, an ITO electrode, a hole transport layer, a photoactive layer, an electron transport layer, and a metal electrode arranged in sequence; or the solar cell may include a substrate, an ITO electrode, an electron transport layer, a photoactive layer, a hole transport layer, and a metal electrode arranged in sequence.
[0026] Optionally, the electrode ITO material is indium tin oxide; the hole transport layer material is selected from PEDOT:PSS, 2PACz, 4PACz, Poly-4PACz, MeO-4PACz, Ph-4PACz (Formula IX) or MoO3, with a thickness of 1~5 nm; the electron transport layer material is selected from PDINO, PDINN, PNDIT-F3N (Formula X) or ZnO nanoparticles, with a thickness of 5~20 nm; the metal electrode material is selected from Al or Ag, with a thickness of 80~100 nm; and the photoactive layer has a thickness of 70~90 nm.
[0027]
[0028] Formula IX
[0029] Formula X An optional configuration is that the solar cell is in an upright structure when the substrate, ITO electrode, hole transport layer, photoactive layer, electron transport layer and metal electrode are arranged; or the solar cell is in an inverted structure when the substrate, ITO electrode, electron transport layer (5), photoactive layer, hole transport layer and metal electrode are arranged.
[0030] In a further embodiment, the photoactive layer further includes volatile additives selected from one or more combinations of p-diiodobenzene, thieno[3,2-b]thiophene, 2-bromobiphenyl, 2,2'-dibromobiphenyl, trichloropyridine, and 2-naphthonitrile.
[0031] The present invention also provides a method for preparing the above-described organic solar cell containing liquid crystal, the method comprising the following steps: Step 1: Pretreatment of ITO substrate with electrodes: The transparent substrate is ultrasonically cleaned and then plasma cleaned in sequence; Step 2: For the upright structure, spin-coat the hole transport layer on the ITO electrode; for the inverted structure, spin-coat the electron transport layer on the ITO electrode. Step 3: Set a photoactive layer on the hole transport layer or electron transport layer, including dissolving electron donor material, electron acceptor material and liquid crystal compound in a solvent to prepare a photoactive layer mixed solution, uniformly coating the mixed solution onto the electron transport layer by scraping, dropping or spin coating, and then heating and annealing to evaporate the solvent to prepare the photoactive layer; Step 4: For the upright structure, spin-coat an electron transport layer onto the photoactive layer; for the inverted structure, deposit a hole transport layer onto the photoactive layer. Step 5: Deposit metal electrodes on the surface of the electron transport layer or hole transport layer using vacuum evaporation.
[0032] An optional approach is that, in step three, the solvent is selected from one or more of the following: pentane, dichloromethane, carbon disulfide, 1,1-dichloroethane, chloroform, tetrahydrofuran, hexane, trifluoroacetic acid, 1,1,1-trichloroethane, carbon tetrachloride, benzene, acetonitrile, isopropanol, 1,2-dichloroethane, ethylene glycol dimethyl ether, nitromethane, trichloroethylene, toluene, chlorobenzene, 1,4-dioxane, pyridine, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, p-xylene, xylene, o-xylene, N,N-dimethylformamide, cyclohexanone, phenol, 1,2-propanediol, dimethyl sulfoxide, and acetamide; and the heating annealing temperature range is 80~200 °C.
[0033] The organic solar cell provided by this invention comprises electrodes, a charge transport layer, a photoactive layer, another charge transport layer, and a semi-transparent metal electrode arranged in a sequentially stacked manner. The photoactive layer is a mixed thin film made of electron donor material, electron acceptor material, and liquid crystal material. This eliminates the cold crystallization temperature of the film, avoiding the metastable state during the initial formation of the film, thereby enhancing the crystallinity of the film, forming more perfect crystals, and a closer molecular packing distance. This allows for the realization of high-performance, long-life organic solar cells using a simple and low-cost preparation method. Furthermore, the added liquid crystal material does not need to be removed from the active layer through heating or vacuuming, avoiding the complex removal process of volatile additives, simplifying the cell fabrication process, and facilitating large-scale fabrication. Compared with existing technologies, this invention has the following beneficial effects: (1) Fundamentally eliminating the metastable state of the acceptor and achieving thermodynamic locking: Existing additive technologies mainly focus on kinetic regulation, which can only optimize the initial morphology, while the acceptor remains in a metastable state (e.g., cold crystallization peaks are present in the differential scanning calorimetry (DSC) diagram of BTP-eC9). This invention induces the acceptor to directly form a highly ordered molecular stack during film formation through strong intermolecular interactions between nematic liquid crystal molecules and the acceptor, completely eliminating the cold crystallization behavior of the acceptor (the cold crystallization peaks disappear in DSC), so that the photoactive layer is in a thermodynamically stable state at the initial film formation. According to DSC analysis, the cold crystallization enthalpy of the BTP-eC9 acceptor treated with the preferred liquid crystal molecule 3UTPP4 of this invention decreased from -12.24 J / g to 0 at around 195℃, the melting point decreased from 300.03 ℃ to 277.80 ℃, and the melting enthalpy decreased from 24.58 J / g to 13.96 J / g.
[0034] (2) Synergistic enhancement of the crystallographic order of donors and acceptors to achieve efficient charge transport: The nematic liquid crystal molecules in this invention not only regulate the acceptor but also improve the intermolecular aggregation of the polymer donor, reduce the π-π stacking distance, and increase the crystallographic coherence length. As shown by grazing incidence wide-angle X-ray scattering analysis, the π-π stacking distance of the PM6 donor treated with the preferred liquid crystal molecule 3UTPP4 of this invention decreased from 3.747 Å to 3.732 Å, while a higher-order diffraction peak appeared; the π-π stacking distance of the BTP-eC9 acceptor decreased from 3.636 Å to 3.605 Å, and the crystallographic coherence length increased from 16.925 Å to 17.799 Å. This dual enhancement of order effectively promotes charge transport and inhibits bimolecular recombination.
[0035] (3) Achieving synergistic improvement in high efficiency and high stability: The organic solar cell devices prepared by this invention simultaneously achieve significantly improved photoelectric conversion efficiency and excellent long-term stability. For example, in the PM6:BTP-eC9 binary system treated with 3UTPP4, the photoelectric conversion efficiency of the device increased from 18.61% to 19.57%, and the fill factor increased from approximately 78.52% to 80.31%; when combined with diiodobenzene additive, the fill factor was further increased to 80.51%, and the photoelectric conversion efficiency was further increased to 20.07%. In the D18:L8-BO binary system treated with 3UTPP4, when combined with diiodobenzene additive, the photoelectric conversion efficiency of the device was further increased to 20.73%, and the fill factor reached 82.14%. In terms of stability, the device prepared by this invention can still maintain 96% of the initial PCE after being stored in a nitrogen atmosphere for 1600 hours, which is much higher than the 91% of the control device; after being subjected to maximum power point tracking at 45°C and 1 solar intensity for 1000 hours, it can still maintain 81% of the initial efficiency, which is significantly better than the 69% of the control device.
[0036] (4) Strong universality, applicable to a variety of high-performance donor / receptor systems: The method of the present invention has shown significant effects in a variety of high-performance systems such as PM6:Y6, D18:L8-BO, PM6:Y6-BO, and PM6:D18:L8-BO, proving that the strategy has good universality. Attached Figure Description
[0037] Figure 1 This is a schematic diagram (upright) of an organic solar cell structure according to the present invention.
[0038] Figure 2 The present invention relates to the current-voltage curves of the PM6:BTP-eC9:3UTPP4 organic solar cell under standard sunlight (AM1.5G, 1 sun).
[0039] Figure 3 This is the storage lifetime curve of the PM6:BTP-eC9:3UTPP4 organic solar cell of the present invention.
[0040] Figure 4 This is the lifespan curve of the PM6:BTP-eC9:3UTPP4 organic solar cell of the present invention at maximum power.
[0041] Figure 5 The differential scanning calorimetry curves of BTP-eC9 and BTP-eC9:3UTPP4 of the present invention are shown.
[0042] Figure 6These are 2D patterns and 1D tangents of grazing-incidence wide-angle X-ray scattering of PM6, PM6:3UTPP4, BTP-eC9, and BTP-eC9:3UTPP4 of the present invention; (a) is the 2D diffraction pattern of the PM6 film, (b) is the 2D diffraction pattern of the PM6:3UTPP4 film, (c) is the 2D diffraction pattern of the BTP-eC9 film, (d) is the 2D diffraction pattern of the BTP-eC9:3UTPP4 film; and (e) is the 1D tangent of the corresponding film.
[0043] Figure 7 The present invention relates to an organic solar cell with PM6:BTP-eC9:3UTPP4 combined with DIB, and its current-voltage curves under standard sunlight (AM1.5G, 1 sun).
[0044] Figure 8 The present invention relates to an organic solar cell with D18:L8-BO:2UTPP3 combined with DIB, and its current-voltage curves under standard sunlight (AM1.5G, 1 sun). Detailed Implementation
[0045] To make the objectives, features, and advantages of this invention clear and easy to understand, the organic solar cell with liquid crystal molecule regulation of this invention is described in detail below with reference to embodiments and accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the invention. However, the invention can be practiced in many ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below. Technical features in various embodiments of the invention can be combined appropriately without conflict.
[0046] The following examples illustrate the abbreviations for liquid crystal compounds: For the sake of simplicity, the series of liquid crystal compounds involved in this invention are represented by the general formula "nUTPPm", wherein: “n” and “m” each independently represent the number of carbon atoms in the alkyl chain attached to the benzene rings at both ends of the molecule; “U” represents the carbon-carbon triple bond (-C≡C-) that connects the aromatic ring. "TPP" indicates that the core skeleton of the molecule is a para-linked terphenyl structure.
[0047] As an example: "3UTPP4" indicates that the alkyl group at one end of the molecule is propyl (-C3H7, n=3) and the alkyl group at the other end is butyl (-C4H9, m=4). The specific structure of the liquid crystal compound it represents is as follows: .
[0048] "2UTPP3" indicates that one alkyl group at one end of the molecule is ethyl (-C2H5, n=2), and the other alkyl group is propyl (-C3H7, m=3). The specific structure of the liquid crystal compound it represents is as follows: .
[0049] It should be noted that the alkyl chains represented by "n" and "m" can be straight or branched, and are not limited to the specific carbon number combinations in the examples above.
[0050] Example 1: The organic solar cell structure used in Example 1 is ITO / Ph-4PACz / photoactive layer / PNDIT-F3N / Ag. The device area in this example is 0.057 square centimeters, and the shape is rectangular. ITO is the electrode, Ph-4PACz is the hole transport layer, and the photoactive layer comprises PM6, BTP-eC9, and liquid crystal molecule 3UTPP4 in a weight ratio of 1:1.2:0.05, with a melting point of 69.94 °C and a clearing point of 168.89 °C. PNDIT-F3N is the electron transport layer, and Ag is the electrode. The specific fabrication process includes the following steps: First, the ITO glass substrate was plasma cleaned in a plasma cleaner for 2 minutes, and then placed on a spin coater to spin-coat the ITO surface with the self-assembled single-molecule hole transport material Ph-4PACz (i.e., 4-(9H-carbazole-9-yl)phenylphosphonic acid). The spin coater was turned on and the spin coater was turned on at a speed of 3000 rpm for 30 seconds to obtain a self-assembled single-molecule hole transport layer with a thickness of about 2 nanometers. After film formation, the ITO conductive glass substrate coated with Ph-4PACz was placed on a heating stage at 110 °C for annealing to promote further orderly arrangement of molecules. The solution was then transferred to a nitrogen-filled glove box and spin-coated on a spin coater. In this embodiment, the photoactive layer solution was prepared by dissolving PM6, BTP-eC9, and 3UTPP4 in chloroform at a mass ratio of 1:1.2:0.05 to obtain an active layer solution with a PM6 donor concentration of 6 mg / mL. The resulting photoactive layer solution was then coated onto the hole transport layer, and the spin coater was turned on and run at a speed of 2750 rpm. The resulting photoactive layer film had a thickness of 80 nm. The prepared film was then placed on a hot plate at 100 °C for thermal annealing. After the photoactive layer has been stably formed, the electron transport layer PNDIT-F3N, namely a solution of poly[naphthalenedicarboximide-dithiophene]trifluoroethylammonium derivative (solvent is methanol, concentration is 1 mg / mL), is prepared by spin coating to form a thin film with a thickness of 10 nm. It is then moved into a vacuum evaporation chamber, where the vacuum level reaches 3×10⁻⁶. -4After that, a 100-nanometer silver film is deposited as an electrode by thermal evaporation. The battery prepared in this embodiment (with 3UTPP4; PM6:BTP-eC9: 3UTPP4) and the related control (the control (without; PM6:BTP-eC9) differs from the battery in this embodiment in that it does not contain 3UTPP4 liquid crystal molecules) were subjected to current density-voltage (JV) testing under standard sunlight. The testing method referred to the test procedure specified in SEMI PV57, "Test Methods for Current-Voltage Performance of Organic Photovoltaic (OPV) Devices".
[0051] The current density-voltage detection results are attached. Figure 2 As shown, under AM 1.5G and 1 sun conditions, the open-circuit voltage of the organic solar cell containing 3UTPP4 liquid crystal molecules is 0.849 V, and the short-circuit current density is 28.70 mA cm⁻¹. -2 The fill factor is 80.31%, and the photoelectric conversion efficiency is 19.57%. In comparison, the same solar cell without 3UTPP4 liquid crystal molecules has an open-circuit voltage of 0.849 V and a short-circuit current density of 27.92 mA cm⁻¹. -2 The fill factor is 78.52%, and the photoelectric conversion efficiency is 18.61%.
[0052] Storage stability test results are attached. Figure 3 As shown, after being stored in a nitrogen glove box at 25 °C for 1600 hours, the photoelectric conversion efficiency of the battery prepared in this example remained above 95% of its original value.
[0053] The results of the continuous illumination stability test are attached. Figure 4 As shown, after being continuously heated to 45°C and stored for 1000 hours under continuous illumination at the device's maximum power, the photoelectric conversion efficiency of the battery prepared in this embodiment remains above 80% of its initial value, i.e., T80 > 1000 hours.
[0054] In contrast, the same solar cell without 3UTPP4 liquid crystal molecules, when stored in a nitrogen glove box at 25 °C, maintained its photoelectric conversion efficiency of over 95% for approximately 800 hours (compared to 91% after 1600 hours of storage in a nitrogen glove box at 25 °C). Under continuous illumination at maximum power, the T80 of the solar cell without 3UTPP4 liquid crystal molecules, when continuously heated to 45 °C, was 1000 hours.
[0055] DSC analysis was performed on the BTP-eC9 and 3UTPP4 liquid crystal molecule mixture powder with a mass ratio of 1.2:0.05. The results are shown in the figure. Figure 5This indicates that the cold crystallization enthalpy of the BTP-eC9 acceptor treated with the preferred liquid crystal molecule 3UTPP4 of this invention decreased from -12.24 J / g to 0 at around 195°C, the melting point decreased from 300.03°C to 277.80°C, and the melting enthalpy decreased from 24.58 J / g to 13.96 J / g.
[0056] Grazing-incidence wide-angle X-ray scattering analysis was performed on a thin film of a mixture of PM6, BTP-eC9, and 3UTPP4 in a mass ratio of 1:1.2:0.05. The results are shown in [Figure number missing]. Figure 6 The π-π packing distance of the PM6 donor treated with the preferred liquid crystal molecule 3UTPP4 of this invention decreased from 3.747 Å to 3.732 Å, while a higher-order diffraction peak appeared; the π-π packing distance of the BTP-eC9 acceptor decreased from 3.636 Å to 3.605 Å, and the crystal coherence length increased from 16.925 Å to 17.799 Å.
[0057] Example 2: The difference between this embodiment and the battery in Embodiment 1 is that a volatile additive, p-diiodobenzene (DIB), is added to the photoactive layer, and the concentration of DIB in the photoactive layer mixture is 5 mg / mL; the rest of the scheme is the same as in Embodiment 1.
[0058] As attached Figure 7 As shown, under AM 1.5G and 1 sun condition, its open-circuit voltage is 0.854 V and its short-circuit current density is 29.21 mA cm⁻¹. -2 The fill factor was 80.51%, resulting in an efficiency of 20.07%. In comparison, the same cell without 3UTPP4 exhibited an open-circuit voltage of 0.853 V and a short-circuit current density of 28.47 mA cm⁻¹. -2 The fill factor is 79.04%, and the photoelectric conversion efficiency is 19.19%. Compared with the same structured cell containing 3UTPP4 and without volatile additives in Example 1, its performance is an open-circuit voltage of 0.849 V and a short-circuit current density of 28.70 mA cm⁻¹. -2 The fill factor was 80.31%, and the photoelectric conversion efficiency was 19.57%. This indicates that the performance of organic solar cells containing 3UTPP4 liquid crystal molecules can be further improved by combining them with existing volatile additives such as diiodobenzene (DIB).
[0059] Example 3: The liquid crystal molecule 3UTPP4 is effective not only in organic solar cells using PM6 as the donor and BTP-eC9 as the acceptor, but also exhibits good performance in various donor-acceptor combinations. This embodiment differs from Example 1 in that the photoactive layer material is different, but the preparation method is the same as in Example 1.
[0060] This embodiment targets the active layers of: (1) D18: L8-BO: 3UTPP4, (2) PM6: D-L8-BO: 3UTPP4, (3) PM6:Y6: 3UTPP4, (4) PM6: Y6-d2: 3UTPP4, and (5) PM6: Y6-BO: 3UTPP4; the organic solar cell structure is ITO / Ph-4PACz / photoactive layer / PNDIT-F3N / Ag, and the preparation method of each cell is the same as in Example 1, wherein the preparation method of the photoactive layer of each cell is as follows: (1) D18: L8-BO: 3UTPP4: D18: L8-BO: 3UTPP4 in a mass ratio of 1:1:0.05 and DIB with an additive concentration of 5 mg / mL were dissolved in chloroform to obtain an active layer solution with a D18 concentration of 4.5 mg / mL; the control group (D18: L8-BO) was a solution without the addition of liquid crystal molecule 3UTPP4 (containing DIB); (2) PM6: D-L8-BO: 3UTPP4: PM6: L8-BO: 3UTPP4 in a mass ratio of 1:1.2:0.05 and DIB with an additive concentration of 5 mg / mL were dissolved in chloroform to obtain an active layer solution with a PM6 concentration of 6 mg / mL; the control group was a solution without the addition of liquid crystal molecules 3UTPP4. (3) PM6: Y6: 3UTPP4: PM6: Y6: 3UTPP4 in a mass ratio of 1:1.2:0.05 and DIB with an additive concentration of 5 mg / mL were dissolved in chloroform to obtain an active layer solution with a PM6 concentration of 6 mg / mL; the control group was a solution without the addition of liquid crystal molecules 3UTPP4. (4) PM6: Y6-d2: 3UTPP4: PM6: Y6-d2: 3UTPP4 in a mass ratio of 1:1.2:0.05 and DIB with an additive concentration of 5 mg / mL were dissolved in chloroform to obtain an active layer solution with a PM6 concentration of 6 mg / mL; the control group was a solution without the addition of liquid crystal molecules 3UTPP4. (5) PM6: Y6-BO: 3UTPP4: PM6: Y6-BO: 3UTPP4 in a mass ratio of 1:1.2:0.05 and DIB with an additive concentration of 5 mg / mL were dissolved in chloroform to obtain an active layer solution with a PM6 concentration of 6 mg / mL; the control group was a solution without the addition of liquid crystal molecules 3UTPP4.
[0061] The battery preparation method is the same as in Example 1.
[0062] Device performance tests show that the liquid crystal molecule 3UTPP4 exhibits significant photoelectric performance enhancement in multiple systems, and the photovoltaic parameters are shown in Table 1.
[0063] Table 1. Photovoltaic performance parameters of organic solar cells with liquid crystal molecule 3UTPP4 in multiple systems
[0064] Example 4: The difference between this embodiment and Embodiment 1 is that the photoactive layer material is different, but the preparation method is the same as in Embodiment 1.
[0065] The photoactive layer of this embodiment comprises D18, L8-BO, and liquid crystal molecule 2UTPP3 in a weight ratio of 1:1:0.05, wherein the liquid crystal molecule 2UTPP3 has a melting point of 72.09 °C and a clearing point of 176.16 °C. The donor material concentration in the prepared photoactive layer mixed solution is 4.5 mg / mL, and the additive p-diiodobenzene (DIB) concentration is 5 mg / mL.
[0066] Battery performance test results are attached. Figure 8 As shown, under AM 1.5G, 1 sun condition, the open-circuit voltage of the battery prepared in this embodiment is 0.926 V, and the short-circuit current density is 27.52 mA cm⁻¹. -2 The fill factor was 82.03%, resulting in an efficiency of 20.91%. In contrast, the same battery device without liquid crystal molecules (2UTPP3) had an open-circuit voltage of 0.916V and a short-circuit current density of 26.95 mA cm⁻¹. -2 The fill factor was 80.60%, and the final efficiency was 19.89%.
[0067] Example 5: This embodiment differs from Example 1 in that the liquid crystal compound in the photoactive material is different, but the preparation method is the same as in Example 1. The photoactive layer in this embodiment comprises PM6, BTP-eC9, and liquid crystal molecule 3UTPP2 in a weight ratio of 1:1.2:0.05, wherein the 3UTPP2 liquid crystal molecule has a set temperature of 75.64 °C and a clearing point of 176.22 °C. The donor material concentration in the prepared photoactive layer mixed solution is 6 mg / mL.
[0068] Testing showed that, under AM 1.5G and 1 sun conditions, the battery prepared in this embodiment had an open-circuit voltage of 0.851 V and a short-circuit current density of 29.16 mA cm⁻¹. -2 The fill factor was 77.93%, and the final efficiency was 19.33%. In contrast, the same battery device without liquid crystal molecules 3UTPP2 had an open-circuit voltage of 0.850 V and a short-circuit current density of 28.43 mA cm⁻¹. -2 The fill factor was 77.87%, and the final efficiency was 18.83%.
[0069] Example 6: This embodiment differs from Example 1 in that the liquid crystal compound in the photoactive material is different, but the preparation method is the same as in Example 1. In this embodiment, the photoactive layer comprises PM6, BTP-eC9, and liquid crystal molecule 4UTPP3 in a weight ratio of 1:1.2:0.05, wherein the 4UTPP3 liquid crystal molecule has a set temperature of 51.47 °C and a clearing point of 171.84 °C. The donor material concentration in the prepared photoactive layer mixed solution is 6 mg / mL.
[0070] Testing showed that, under AM 1.5G and 1 sun conditions, the battery prepared in this embodiment had an open-circuit voltage of 0.847 V and a short-circuit current density of 28.60 mA cm⁻¹. -2 The fill factor was 78.44%, resulting in an efficiency of 19.00%. In contrast, the same battery device without the liquid crystal molecules 4UTPP3 had an open-circuit voltage of 0.850 V and a short-circuit current density of 28.43 mA cm⁻¹. -2 The fill factor was 77.87%, and the final efficiency was 18.83%.
[0071] Example 7: This embodiment differs from Example 1 in that the liquid crystal compound in the photoactive material is different, but the preparation method is the same as in Example 1. In this embodiment, the photoactive layer comprises PM6, BTP-eC9, and liquid crystal molecule 5UTPP3 in a weight ratio of 1:1.2:0.05, wherein the melting point of the liquid crystal molecule 5UTPP3 is 69.09 °C and the clearing point is 174.93 °C. The donor material concentration in the prepared photoactive layer mixed solution is 6 mg / mL.
[0072] Testing showed that, under AM 1.5G and 1 sun conditions, the battery prepared in this example had an open-circuit voltage of 0.840 V and a short-circuit current density of 28.87 mA cm⁻¹. -2 The fill factor was 77.19%, resulting in an efficiency of 18.73%. In contrast, the same battery device without liquid crystal molecules (5UTPP3) had an open-circuit voltage of 0.850 V and a short-circuit current density of 28.43 mA cm⁻¹. -2 The fill factor was 77.87%, and the final efficiency was 18.83%.
[0073] Although this application has been described above with reference to specific embodiments, those skilled in the art will understand that many modifications can be made to the configurations and details disclosed herein within the principles and scope of the present application. The scope of protection of this invention is determined by the appended claims, and the claims are intended to cover all modifications included in the literal meaning or scope of equivalents of the technical features in the claims.
Claims
1. An organic solar cell containing liquid crystal, characterized in that, The photoactive layer of the organic solar cell comprises an electron donor material, an electron acceptor material, and a liquid crystal compound, wherein the general structural formula of the liquid crystal compound is Formula I: Formula I Where R1 and R2 are each independently C1-C 10 Straight-chain alkyl or C1-C 10 Branched alkyl groups.
2. The organic solar cell containing liquid crystal according to claim 1, characterized in that, The melting point of the liquid crystal molecules is 30~100 °C, and the clearing point is 100~180 °C.
3. The organic solar cell containing liquid crystal according to claim 1, characterized in that, When R1 is propyl and R2 is butyl, the structural formula of the liquid crystal compound is Formula II: Formula II.
4. The organic solar cell containing liquid crystal according to claim 1, characterized in that, When R1 is ethyl and R2 is propyl, the structural formula of the liquid crystal molecule is Formula III: Formula III.
5. The organic solar cell containing liquid crystal according to claim 1, characterized in that, When R1 is propyl and R2 is ethyl, the structural formula of the liquid crystal compound is Formula IV: Formula IV.
6. The organic solar cell containing liquid crystal according to claim 1, characterized in that, When R1 is butyl and R2 is propyl, the structural formula of the liquid crystal compound is formula V: Formula V.
7. The organic solar cell containing liquid crystal according to claim 1, characterized in that, When R1 is pentyl and R2 is propyl, the liquid crystal compound has the structural formula of formula VI: Formula VI.
8. The organic solar cell containing liquid crystal according to claim 1, characterized in that, The electron donor material is one or a combination of two or more of D18, PM6, PTQ10, D18-Cl, P3HT, PTB7-Th, PTB7, PBDB-T, and J52; the electron acceptor material is one or a combination of two or more of Y6, BTP-eC9, L8-BO, Y6-BO, BTP-eC11, BTP-4Cl, N3, PYT, and PY-IT.
9. The organic solar cell containing liquid crystal according to claim 1, characterized in that, The mass ratio of electron donor material to electron acceptor material is 1:1 to 1:1.3, and the amount of liquid crystal molecules added is 1% to 10% of the mass of electron donor material.
10. The organic solar cell containing liquid crystal according to claim 1, characterized in that, The solar cell includes a substrate (1), an ITO electrode (2), a hole transport layer (3), a photoactive layer (4), an electron transport layer (5), and a metal electrode (6) arranged in sequence; or the solar cell includes a substrate (1), an ITO electrode (2), an electron transport layer (5), a photoactive layer (4), a hole transport layer (3), and a metal electrode (6) arranged in sequence.
11. The organic solar cell containing liquid crystal according to claim 10, characterized in that, The electrode ITO (2) material is indium tin oxide; the hole transport layer (3) material is selected from PEDOT:PSS, 2PACz, 4PACz, Poly-4PACz, MeO-4PACz, Ph-4PACz or MoO3, with a thickness of 1~5 nm; the electron transport layer (5) material is selected from PDINO, PDINN, PNDIT-F3N or ZnO nanoparticles, with a thickness of 5~20 nm; the metal electrode (6) material is selected from Al or Ag, with a thickness of 80~100 nm; the photoactive layer thickness is 70~90 nm.
12. The organic solar cell containing liquid crystal according to claim 10, characterized in that, The solar cell is in an upright structure when the substrate (1), ITO electrode (2), hole transport layer (3), photoactive layer (4), electron transport layer (5) and metal electrode (6) are arranged; the solar cell is in an inverted structure when the substrate (1), ITO electrode (2), electron transport layer (5), photoactive layer (4), hole transport layer (3) and metal electrode (6) are arranged.
13. The organic solar cell containing liquid crystal according to any one of claims 1 to 11, characterized in that, The photoactive layer further includes volatile additives selected from one or more of p-diiodobenzene, thieno[3,2-b]thiophene, 2-bromobiphenyl, 2,2'-dibromobiphenyl, trichloropyridine, and 2-naphthonitrile.
14. The method for preparing the organic solar cell containing liquid crystal according to claim 1, characterized in that, The preparation method includes the following steps: Step 1: Pretreatment of ITO substrate with electrodes: The transparent substrate is ultrasonically cleaned and then plasma cleaned in sequence; Step 2: For the upright structure, spin-coat the hole transport layer on the ITO electrode; for the inverted structure, spin-coat the electron transport layer on the ITO electrode. Step 3: Set a photoactive layer on the hole transport layer or electron transport layer, including dissolving electron donor material, electron acceptor material and liquid crystal compound in a solvent to prepare a photoactive layer mixed solution, uniformly coating the mixed solution onto the electron transport layer by scraping, dropping or spin coating, and then heating and annealing to evaporate the solvent to prepare the photoactive layer; Step 4: For the upright structure, spin-coat an electron transport layer onto the photoactive layer; for the inverted structure, deposit a hole transport layer onto the photoactive layer. Step 5: Deposit metal electrodes on the surface of the electron transport layer or hole transport layer using vacuum evaporation.
15. The organic solar cell containing liquid crystal as described in claim 14 and its preparation method, characterized in that, In step three, the solvent is selected from one or more of the following: pentane, dichloromethane, carbon disulfide, 1,1-dichloroethane, chloroform, tetrahydrofuran, hexane, trifluoroacetic acid, 1,1,1-trichloroethane, carbon tetrachloride, benzene, acetonitrile, isopropanol, 1,2-dichloroethane, ethylene glycol dimethyl ether, nitromethane, trichloroethylene, toluene, chlorobenzene, 1,4-dioxane, pyridine, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, p-xylene, xylene, o-xylene, N,N-dimethylformamide, cyclohexanone, phenol, 1,2-propanediol, dimethyl sulfoxide, and acetamide; the heating annealing temperature range is 80~200 °C.